Touch me if you dare: tactility in media art. (1st January 2011) - Wilson, Laetitia
Physical computing has enabled artists to take the experience of data beyond the screen and into the materiality of the world of things. Novel interface structures, in recent media art practice, are defying the traditional interface of mouse and joystick to engage the corporeality of the participant in sensuous as well as physically compromising ways. This paper takes a phenomenological perspective from which to critically engage in a discussion of tactility in media art against a background of three case studies that optimise sensory stimuli in the form of moisture, softness and the effect of stimulation in the form of pain. This primary focus of the discussion will be couched in a consideration of how media art interfaces are distinguished from those of traditional art in terms of the nuances of participation demanded by the particular interface in question.